Study on the Key Technology of Controlling the Instability of Deep High-Stress Coal and Rock Mass and Relieving the Danger - Zhijing Zhang; Jianghong Zuo; Dongji Lei (Advances in Civil Engineering)
In order to solve the problem of stress concentration and gas overrun in the process of uncovering high gas and thick coal seam, combined with the occurrence characteristics of coal seams in Wuyang Coal Mine, the measures of “hydraulic and mechanical cavity making + steel screen pipe + surrounding rock grouting” are adopted to establish a method for mutual verification of multiple effect test indexes of residual stress, residual gas content, coal seam moisture content, and microseismic signal characteristics, and the three-dimensional accurate analysis of the influence range of hydraulic cavitation is effectively realized. By comparing and analyzing the gas extraction amount, the surrounding borehole stress change and the microseismic monitoring signals before and after the application of hydraulic cavitation technology are studied. The results show the following. (1) The pressure relief effect of the hydraulic cavity on surrounding coal decreases with the increase of distance, and the pressure relief effect is most obvious at 1.0∼2.5 m, in the range of 2.5–3.5 m around the hydraulic drilling hole, the duration, rate, and amplitude of pressure relief are reduced compared with those in the range of less than 2.5 m, while in the range of more than 3.5 m, the effect of pressure relief is very weak. (2) During the period of hydraulic cavitation release hole, the radius of water supply to coal seam is within 1.5 m, which accounts for 79% of coal wall area. (3) It is also a process where the stress distribution in the coal and rock body needs to be rebalanced before and after hydraulic caverning, which is often accompanied by microfracture of coal and rock mass. The analysis shows that, before hydraulic caverning, the waveform of coal and rock fracture signal has a short duration, large amplitude, and obvious signal mutation, and the dominant frequency of the signal is about 250 Hz, with large total energy. After hydraulic caverning, the intensity of coal and rock fracture events is greatly reduced. The research results can effectively identify the influence range of hydraulic cavitation, improve the detection accuracy and efficiency of hydraulic cavitation range, effectively predict and warn the hidden danger of mine safety, and provide a reference for the work of similar mines.